Guidance Management Counseling in Students' Moral Education in MAN Jombang Academic Year 2019/2020 - Moh. Ifan Fahmi (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
This study aims to determine the tasks, strategies, and role of guidance and counseling teachers in MAN Jombang, as well as what factors are obstacles and supporters of the implementation of guidance and counseling programs in the moral education of students at MAN Jombang. This research is a case study research using qualitative methods that are descriptive. The object of his research is everything related to the guidance and counseling teacher at MAN Jombang. Our data sources can be from school principals, vice principals, homeroom teachers, field study teachers, counseling guidance teachers, and from students. Data collection techniques using interview and observation techniques. The data analysis technique uses qualitative descriptive analysis techniques. As for testing the validity of our data, we use triangulation techniques. The results of this study explain that (1) The task of guidance and counseling teachers in the moral education of students in MAN Jombang, is to help students become human beings who believe, devote to God Almighty, and direct students to behave in society, lead students to know the talents, interests, and direction of future career trends, and solve all problems faced by students. (2) The strategy of implementing guidance and counseling in the moral education of students in MAN Jombang, can not be separated from the 4 important components that support each other, namely: basic services, responsive services, individual planning, and system support. (3) The role of guidance and counseling in the moral education of students in MAN Jombang, is very important for students to provide assistance, and direction to students, so that they can become useful human beings for the homeland and the nation. (4) Factors inhibiting the implementation of guidance and counseling programs in the moral education of students in MAN Jombang, can come from teachers, homeroom teachers, parents and students, (5) Factors supporting the implementation of guidance and counseling programs in the moral education of students in MAN Jombang, namely school principals, field studies teachers, homeroom teachers, parents, case handlers and adequate infrastructure, all of which are mutually reinforcing factors.